Eudaimonia: Elaborasi Filosofis Konsep Kebahagiaan Aristoteles dan Yuval Noah Harari - Benito Cahyo Nugroho (Parahyangan Catholic University, 2020)
Ever has man sought happiness to enrich his days, to such lengths that twould not be an understatement to state happiness is his life’s goal. Aristotle defines happiness as eudaimonia, a goal which must be achieved by any means, whilst Harari offers the definition as a process of knowing oneself but even so a meeting point between the two I claim may be possible particularly in this day and age in order to seek and achieve hap- piness. As one may derive from the meeting point, both agree happiness is not limited to the simple fulfillment of physical needs. Happiness possesses an internal dimension, wrought once one lives a wholesome existence in concord to ones vocation.